2021
DOI: 10.1002/advs.202004504
|View full text |Cite
|
Sign up to set email alerts
|

OTUD7B Deubiquitinates LSD1 to Govern Its Binding Partner Specificity, Homeostasis, and Breast Cancer Metastasis

Abstract: Genomic amplification of OTUD7B is frequently found across human cancers. But its role in tumorigenesis is poorly understood. Lysine‐specific demethylase 1 (LSD1) is known to execute epigenetic regulation by forming corepressor complex with CoREST/histone deacetylases (HDACs). However, the molecular mechanisms by which cells maintain LSD1/CoREST complex integrity are unknown. Here, it is reported that LSD1 protein undergoes K63‐linked polyubiquitination. OTUD7B is responsible for LSD1 deubiquitination at K226/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 67 publications
0
23
0
Order By: Relevance
“…For validation, we performed cotransfection with the Flag‐tagged NR6A1 and HA‐tagged K48, K11, and K0 Ub mutant plasmids into the rat primary VSMCs (K0 plasmid refers to the mutation of all seven Ks on the ubiquitin molecule into R, so that it can be assembled into a linear ubiquitin chain from the first methionine [M1]). [ 26 ] Next, IP for Flag was conducted, with the results showing that the main ubiquitination type of NR6A1 was M1 linear ubiquitination (Figure 4A). Literature has shown that the only E3 ubiquitin ligase complex involved in linear ubiquitination is LUBAC, and the LUBAC complex is predominantly composed of HOIP (RNF31), HOIL‐1 (RBCK1), and SHANRPIN.…”
Section: Resultsmentioning
confidence: 99%
“…For validation, we performed cotransfection with the Flag‐tagged NR6A1 and HA‐tagged K48, K11, and K0 Ub mutant plasmids into the rat primary VSMCs (K0 plasmid refers to the mutation of all seven Ks on the ubiquitin molecule into R, so that it can be assembled into a linear ubiquitin chain from the first methionine [M1]). [ 26 ] Next, IP for Flag was conducted, with the results showing that the main ubiquitination type of NR6A1 was M1 linear ubiquitination (Figure 4A). Literature has shown that the only E3 ubiquitin ligase complex involved in linear ubiquitination is LUBAC, and the LUBAC complex is predominantly composed of HOIP (RNF31), HOIL‐1 (RBCK1), and SHANRPIN.…”
Section: Resultsmentioning
confidence: 99%
“…Mounting evidence supports that LSD1 is overexpressed in many subtypes of BC and promotes their proliferation (Pollock et al, 2012;Yang et al, 2018d;Xu et al, 2019;Wang et al, 2022), differentiation (Wu et al, 2013;Zhang et al, 2013;Ji et al, 2021), metastasis (Li et al, 2011;Qiu et al, 2018;Zheng et al, 2018;Hu et al, 2019;Gong et al, 2021), and drug resistance (Bennani-Baiti, 2012;Verigos et al, 2019;Zhou et al, 2021a;Liu et al, 2022), which makes LSD1 become a promising target for BC therapy. But the detailed mechanisms of the LSD1 in BC progression are unclear and more potential anti-tumor pathways or downstream genes are yet to clarify due to the heterogeneity of varieties of BC subtypes.…”
Section: Dual-target Inhibitors and Combined Therapymentioning
confidence: 98%
“…For example, miR-708 inhibits BC proliferation and invasion via directly binding to the 3′ UTR of LSD1 and reducing its level (Ma et al, 2016). In addition, epigenetic modifications such as phosphorylation (Peng et al, 2015;Feng et al, 2016;Zhou et al, 2016), acetylation (Luo et al, 2016), methylation (Liu et al, 2020a), and ubiquitination (Wu et al, 2013;Yi et al, 2016;Zhou et al, 2016;Gong et al, 2021) also contribute to the function of LSD1 (Figure 2). PKCα can phosphorylate LSD1 at S112, activating its demethylase activity and enhancing the occupancy on E-cadherin promoter, and finally promote EMT and metastasis in BC (Feng et al, 2016).…”
Section: The Epigenetic Regulation Of Lsd1mentioning
confidence: 99%
See 2 more Smart Citations